Improving an analytical model of the near magnetic field of electromagnets in the spacecraft orientation control system - Getman, Andriy; Konstantinov, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2025)
The specificity of applying the technology for ensuring magnetic purity of small spacecraft, which have cylindrical electromagnets with a magnetic moment of 10–50 A m2 in the orbit orientation control system, has been considered. It is shown that the electromagnets of the orientation control system are the most powerful source of magnetic hindrance with a magnetic flux density of up to 1 T for the magnetically sensitive equipment of the spacecraft. The need for modeling the magnetic field of the electromagnet at the preliminary stage of spacecraft development for the rational choice of its layout has been substantiated. In order to improve the technology for ensuring magnetic purity, which is aimed at increasing the reliability of spacecraft operation, a search for the best model of the magnetic field of such electromagnets was carried out. A comparative analysis of approximate analytical models of the near magnetic field of a cylindrical electromagnet, which are based on its magnetic moment and overall dimensions, was carried out. It is established that the model based on two shifted dipole moments and the multipole model have unacceptably large deviations in the results of calculating the near magnetic field near the body of a cylindrical electromagnet. The advantages in the form of an expanded application area and a reduced deviation of the near magnetic field representation to 5 % when using the model based on cylindrical harmonics of the electromagnet have been theoretically substantiated. Formulas for engineering calculation of the magnetic field induced by a cylindrical electromagnet inside the spacecraft using its improved analytical model have been derived. It is proposed to use the model based on cylindrical harmonics for preliminary calculation of the magnetic hindrance generated by the electromagnets of the orientation control system to the magnetically sensitive equipment of the spacecraft